Correspondence regarding "Ventilatory efficiency in athletes, asthma and obesity": different ventilatory phenotypes during exercise in obesity?. (29th June 2022) - Borasio, Nicola; Vecchiato, Marco; Quinto, Giulia; Battista, Francesca; Neunhaeuserer, Daniel; Ermolao, Andrea
Collins et al . [1] discussed the pathophysiological mechanisms and clinical relevance of ventilatory efficiency in athletes, asthma and obesity in their interesting review article entitled "Ventilatory efficiency in athletes, asthma and obesity". Patients with obesity can display an altered ventilatory response to exercise, which may contribute to functional limitations in this population. We aim to provide a supplementary contribution to the clinical evaluation and pathophysiological interpretation of the ventilatory response to exercise in patients with obesity. This contribution resulted from two papers recently published by our research group. Patients with obesity may have different ventilatory phenotypes during exercise related to an interaction of expiratory flow limitation, mechanical constraints and adaptations of chemoreception and metabolic setpoints. https://bit.ly/3JBs86S